The Potentials of Two Underutilized Acidic Fruits (Averrhoa bilimbi L. and Phyllanthus acidus L.) as Phytobiotics for Broiler Chickens - Sugiharto, Sugiharto (Journal of Advanced Veterinary Research, 2020)
Phytobiotics have attracted considerable interest as the substitutes for subtherapeutic antibiotics in broiler production. Among the phytobiotics, Averrhoa bilimbi L. and Phyllanthus acidus L. fruits seem to have potential to be developed. Both underutilized acidic fruits contain several bioactive components that may serve as antimicrobial agents, antioxidants, immunomodulators and acidifier, which are beneficial for broiler performance and health. The bioactive components responsible for as well as the mechanisms through which the components exert the phytobiotic activities are highlighted in the present review. The current application of A. bilimbi and P. acidus fruits in broiler production is also presented. Overall, although A. bilimbi and P. acidus fruits show phytobiotic properties, they are still less utilized by the farmers to improve the growth and health performance of broiler chickens